Recent Trends of Functional Nanomaterials for Biomedical and Healthcare Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
We explore the cutting-edge realm of 'Recent Trends in Functional Nanomaterials for Biomedical and Healthcare Applications' through this insightful reprint. Morever, we delve into the new advancements in nanotechnology where functional nanomaterials are revolutionizing biomedicine and healthcare. This reprint uncovers the latest advancements, applications, and the transformative potential of these nanomaterials, offering a glimpse into the future of healthcare innovation. From targeted drug delivery to advanced imaging technologies, this reprint captures the essence of how nanomaterials are reshaping the landscape of modern healthcare